Comparative analysis of Illumina, PacBio, and nanopore for 16S rRNA gene sequencing of rabbit’s gut microbiota - Biada, Iliyass; Santacreu, María Antonia; González-Recio, Oscar; Ibáñez-Escriche, Noelia (Frontiers in Microbiomes, 2025)
This research aims to assess whether sequencing the full length of the 16S rRNA gene using PacBio HiFi sequencing and Oxford Nanopore Technology (ONT) platforms outperform Illumina MiSeq platform in providing detailed specie level insights. Moreover, it aims to compare the similarities in microbial communities detected across the three platforms. The study employed DNA from four rabbit does’ soft feces, sequenced using Illumina MiSeq for specific 16S rRNA gene regions V3-V4, and for the complete gene sequencing using PacBio HiFi and ONT MinION. Results highlight different levels of taxonomic resolution. At the species level, PacBio and ONT exhibited the better resolutions with 63% and 76% respectively, while 48% for Illumina. However, across all three platforms, the classification output at species level was mainly labeled as “Uncultured_bacterium” for most of the classified sequences, which does not improve the understanding of the gut microbiota composition in rabbits. Moreover, although high correlations between relative abundances of taxa were observed, diversity analysis showed significant differences between the taxonomic compositions of the three platforms. These findings suggest that while PacBio and ONT offer improvements in species-level resolution compared to Illumina, due to references databases ambiguous annotation, all three platforms still fall short in providing a precise species level characterization of the gut microbiota composition in rabbits. Additionally, the disparities observed across the results from these platforms highlight the significant impact of sequencing platform, especially when different primers are used. This consideration is particularly important when comparing or analyzing sequences derived from different sequencing technologies.